Model Inquiry Berbasis Jelajah Alam Sekitar untuk Meningkatkan Hasil Belajar Siswa SD - Yuyun Dwi Haryanti; Yeni Dwi Kurino; Ujiati Cahyaningsih (Universitas Sebelas Maret, 2020)
Student learning outcomes are still low which have not been developed optimally in the learning process. Learning still emphasizes the cognitive realm while the affective and psychomotor domains of students are ruled out. The purpose of this study was to improve learning outcomes including the cognitive, affective, and psychomotor domains of fifth grade students at elementary school of Sukarajakulon IV. This research is a Class Action Research covering the steps: planning, implementing, observing, and reflecting. Data collection techniques used were tests, observations, and documentation. Data were analyzed descriptively quantitative and qualitative. In the initial conditions students' mastery learning only reached 30%, the first cycle of student learning completeness increased to 75%, and the second cycle of student learning completeness reached 95%. The results of the study show that through Inquiry Model Based on Roaming Nature around can significantly improve student learning outcomes.